SOLVING PROBLEMS IN ATTRACTING AND FINANCING INVESTMENTS IN THE SERVICE SECTOR (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article will consider specific problems associated with attracting and financing investments in the service sector. Focusing on the intangible nature of services, the debate explores the landscape of lack of material assets for collateral, uncertainty in predicting returns, regulatory complications, and dynamic competition.